UKRAINE'S POST-WAR SOLIDARIZATION BASED ON INTERNATIONAL AND EU APPROACHES - Burlai, Tatiana; Kostrytsia, Vasyl (Economy and Sociology, 2025)
The relevance of this article stems from the urgent need to strengthen social solidarity within Ukrainian society, recognized as a key factor in enhancing the country’s socio-economic resilience during martial law and in the post-war period. The aim of the study is to develop a strategic framework for reinforcing post-war solidarity in Ukraine, along with identifying the prerequisites for its tactical implementation, drawing on contemporary international and pan-European approaches. The research adopts an interdisciplinary methodology, incorporating tools from sociology, economic theory, and public administration. The authors have obtained the following key findings: a discernible decline in the level of solidarity among Ukrainians amid the prolonged full-scale war; identification of the primary endogenous risks linked to diminishing societal cohesion; analysis of the post-conflict recovery experiences of various European states, highlighting critical challenges they encountered in restoring solidarity—insights that are highly relevant for Ukraine; and substantiation of the most effective strategic and tactical public governance approaches for fostering national unity. Within the frameworks of economic theory and public administration, the study substantiates that, in alignment with Ukraine’s European integration goals and post-conflict recovery agenda, and in pursuit of a synergistic effect through integrative policy application, the most suitable public governance approaches include: the "Humanitarian Aid–Development–Peace Nexus", the formation of a "social quality perspective", and principles derived from modern EU cohesion policy. The scientific contribution of the article lies in its potential to inform the formulation of strategic directions for Ukraine’s state policy in the context of post-war recovery and comprehensive integration into the European Union.